Audiologic Manifestations of Marshall Syndrome. Issue 8 (September 2018) - Bacciu, Andrea; Di Lella, Filippo; Iaccarino, Ilaria; Pasanisi, Enrico; Fava, Giovanni; Vincenti, Vincenzo; Falcioni, Maurizio
Abstract : Objective: Marshall syndrome is a genetic disorder caused by mutations in the COL11A1 gene. This syndrome is characterized by skeletal, ophthalmologic, craniofacial, and auditory abnormalities. Hearing loss is among the main manifestations reported in this disorder being observed in approximately 80% of affected individuals. The present study aims to describe the audiologic characteristics of three members of a family with Marshall syndrome and also serves as a review of the literature. Study Design: Family study. Setting: Tertiary care otology and skull base center. Patients: We report the audiologic findings in a family with Marshall syndrome consisting of a mother and her son and daughter. Intervention(s): The audiologic evaluation included tympanometry, acoustic reflexes testing, auditory brainstem response, transient otoacoustic emissions, pure-tone audiometry, speech audiometry in quiet, and conditioned play audiometry. These methods were applied according to the age of the patients. In addition, we provide a review of the English-language literature in an attempt to clarify the auditory phenotype of this syndrome. Results: All 3 affected individuals had heterozygous c.3816+1G>A mutation in the splicing donor site of intron 50 of the COL11A1 gene. All three patients in our study had bilateral sensorineural hearing loss. Hearing impairment ranged from mild to moderate in the daughter, moderate in the son, and from mild to moderate in their mother. Conclusion: The majority of individuals with Marshall syndrome present early-onset bilateral sensorineural hearing loss. Hearing impairment is usually detected in early childhood, progresses gradually, and becomes stable in late adulthood, with a severity ranging from mild to severe.